2000
DOI: 10.1097/00000542-200001000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal Cardiac Output Monitor

Abstract: Endotracheal CO monitor is a promising technology that needs further evaluation in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…All patients were intubated with a 7.5-mm ECOM endotracheal tube (ECOM-ETT 7.5 G, ConMed, Utica, NY) after the induction of general anesthesia. This endotracheal tube is specially designed and contains seven silver electrodes on the cuff and tube that continuously measure the bioimpedance signal from the ascending aorta, in close proximity to the trachea [11]. After processing, it provides real-time continuous stroke volume and cardiac index values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients were intubated with a 7.5-mm ECOM endotracheal tube (ECOM-ETT 7.5 G, ConMed, Utica, NY) after the induction of general anesthesia. This endotracheal tube is specially designed and contains seven silver electrodes on the cuff and tube that continuously measure the bioimpedance signal from the ascending aorta, in close proximity to the trachea [11]. After processing, it provides real-time continuous stroke volume and cardiac index values.…”
Section: Methodsmentioning
confidence: 99%
“…The ECOM device was first evaluated in an animal study, which suggested this new technology was both promising and safe [11]. Since then, validation studies have been scarcely reported in humans [12-14].…”
Section: Introductionmentioning
confidence: 99%
“…Because the tracheal mucosa produces mucous and fluid, the endotracheal cardiac output monitor (ECOM) electrodes have been designed to reduce the effects of fluid and mucous buildup. This device appears promising, and preliminary data indicate adequate reliability of this device [49-51]. The main disadvantage of ECOM is the need for an endotracheal tube and mechanical ventilation.…”
Section: Reviewmentioning
confidence: 99%
“…Increased blood flow in the aorta leads to decreased impedance. Apart from CO, also displayed are HR, ECG waveforms, SV, CI, and SVR [120]. …”
Section: Endotracheal Cardiac Output Monitormentioning
confidence: 99%
“…A porcine study found excellent correlation when compared with transit time flow probes [120]. A study in cardiac-surgery patients reported poor correlation with TD, wide limits of agreement and a large percentage error [121].…”
Section: Endotracheal Cardiac Output Monitormentioning
confidence: 99%